Strange Attractors : Signs of Chaos. (New York : The New Museum of Contemporary Art, 1989)
Welling, James ; Wagner, Sukhi ; Hodgkin, Carter ; Reynolds, Dan ; Noble, Alastair ; Cokes, Tony ; Miller, Steve ; Wasow, Oliver ; Clark, Kathryn ; Levine, Jill ; Kessler, Jon ; etc.
Strange Attractors : Signs of Chaos, The New Museum of Contemporary Art, New York, September 14 - November 26, 1989
boek